Tension band wiring and plate fixation for Olecranon fractures: a systematic review and meta-analysis - Mikhail A. Bethell, MS; Tom R. Doyle, MB, MCh; Eoghan T. Hurley, MB, MCh, PhD; Harvey Allen, BS; Tyler S. Pidgeon, MD; Christian A. Péan, MD, MS; Oke Anakwenze, MD, MBA; Christopher S. Klifto, MD (JSES Reviews, Reports, and Techniques, 2025)
Background: The purpose of this study is to perform a systematic review of the literature comparing the utilization of tension-band wiring (TBW) and plate fixation for the surgical management of olecranon fractures. Methods: A systematic search of articles in PubMed and Embase databases was carried out according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies comparing TBW to plate fixation for olecranon fractures were included. All statistical analyses were performed using Review Manager. A P value of < .05 was considered to be statistically significant. Results: Twenty studies with 2164 patients were included. There were no significant differences in the Disabilities of the Arm, Shoulder, and Hand score (12.3 ± 4.7 vs. 12.1 ± 4.9, P = .23), Mayo Elbow Performance score (92.0 ± 5.4 vs. 92.3 ± 3.7, P = .65), or overall range of motion (P = .15) between TBW and plate fixation. Although extension was statistically significant (7° ± 2° vs. 9° ± 2°, P = .05), the 2-degree difference is not clinically meaningful. There were significantly lower rates of loss of reduction (6.6% vs. 2.6%, P < .01), implant removal (31.4% vs. 14.3%, P < .01), overall reoperation (35.3% vs. 17.7%, P < .01), and complications (45.1% vs. 27.6%, P < .01) after plate fixation. Finally, there were no significant differences in wound breakdown (4.4% vs. 3.9%, P = .73) and infection rates (4.1% vs. 4.0%, P = .86). Conclusion: This study highlights that while TBW and plate fixation offer similar functional outcomes for olecranon fractures, plate fixation demonstrates superior results in terms of lower rates of fixation failure, implant removal, reoperation, and overall complications compared to TBW. These findings suggest that plate fixation should be preferred for surgical management for most patients.